1995
DOI: 10.1128/jvi.69.6.3838-3847.1995
|View full text |Cite
|
Sign up to set email alerts
|

Selective depletion of stored calcium by thapsigargin blocks rotavirus maturation but not the cytopathic effect

Abstract: Rotavirus matures inside the endoplasmic reticulum (ER), a site of intracellular calcium storage. Total cell Ca 2؉ depletion has been shown to impair virus maturation, arresting this process at the membrane-enveloped intermediate form following its budding into the ER. On the other hand, rotavirus infection leads to an increase in the internal Ca 2؉ concentration ([Ca 2؉ ] i) and sequestered Ca 2؉ pools. We have used thapsigargin, an inhibitor of the Ca 2؉-ATPase of the ER, to release stored Ca 2؉ and to study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(34 citation statements)
references
References 42 publications
1
32
0
Order By: Relevance
“…NSP4 increases ER membrane permeability to calcium without blocking SERCAmediated calcium uptake (27,28). In contrast, Michelangeli et al (29) reported that TG treatment reduces virus yield due to improper VP7 assembly onto particles, which was attributed to TG blocking calcium uptake rather than the indirect elevation in cytosolic calcium. Our data show that NSP4 viroporin-mediated increases in cytoplasmic calcium activate a specific calcium-induced signaling pathway to initiate autophagy, which enables trafficking of NSP4 and VP7 to viroplasms for subsequent virus assembly.…”
Section: Discussionmentioning
confidence: 97%
“…NSP4 increases ER membrane permeability to calcium without blocking SERCAmediated calcium uptake (27,28). In contrast, Michelangeli et al (29) reported that TG treatment reduces virus yield due to improper VP7 assembly onto particles, which was attributed to TG blocking calcium uptake rather than the indirect elevation in cytosolic calcium. Our data show that NSP4 viroporin-mediated increases in cytoplasmic calcium activate a specific calcium-induced signaling pathway to initiate autophagy, which enables trafficking of NSP4 and VP7 to viroplasms for subsequent virus assembly.…”
Section: Discussionmentioning
confidence: 97%
“…These lines of evidence suggest that rotavirus-induced external Ca 2+ entry pathway is characteristic of a Ca 2+ channel rather than nonselective impairment of the plasma membrane. Such early activation of Ca 2+ entry is speculated to maintain an elevated ER Ca 2+ pool that is required for virion maturation and stability [47,48].…”
Section: Voc and Rocmentioning
confidence: 99%
“…Among these perturbances is a progressive increase in Ca 2+ membrane permeability which leads to an elevation of cytosolic Ca 2÷ concentration and sequestered pools, without an apparent failure of regulatory mechanisms in virus-infected MA104, HT29 and Caco-2 cells (Brunet et al, 2000a;Michelangeli et al, 1991;Perez et al, 1999). In parallel to the increase in plasma membrane permeability and cytosolic Ca 2+ concentration, there is an enhancement of ER sequestered Ca 2+ stores (Brunet et al, 2000a;Michelangeli et al, 1995;Perez et al, 1999). This effect is likely to be due to the activation of ER Ca 2÷ pumps.…”
Section: Rotavirus As a Model For The Genesis Of Viral Diarrheamentioning
confidence: 99%